(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2026)
According to Kuskis and Logan (2013), one of Marshall McLuhan’s main concerns was education, although he is not widely recognized for his studies in this field. Despite having published only two books specifically on the subject, his ideas can be accessed through lectures, interviews, and other media appearances. Based on detailed research conducted in libraries in Canada, McLuhan’s home country, this paper aims to identify possible connections between the ideas of Freire and McLuhan, as well as to explore the aspects that distinguish them. By applying the Laws of Media (McLuhan, M.; McLuhan, E., 1988) to Freirean and McLuhanian thought, considering the classroom as a medium, it is concluded that McLuhan can be seen as an educommunicator and that his studies offer significant contributions to the field of Educommunication.